1995
DOI: 10.1115/1.2838662
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer from High-Frequency to Low-Frequency Modes in Structures

Abstract: A perspective of the mechanisms by which energy is transferred from high- to low-frequency modes is presented. The focus is on some recent experiments that reveal how a low-amplitude high-frequency excitation can produce a large-amplitude low-frequency response. Such a phenomenon is potentially harmful, if not catastrophic. Specifically, these experiments clarify the role of internal resonances, combination external and parametric resonances, and the interactions among modes of widely spaced frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…We use the term non-resonant to distinguish from commonly studied one-to-one, one-to-two, and oneto-three resonances. This type of nonlinear modal coupling was first studied by Nayfeh & Nayfeh (1992) in structural systems. For structural systems, which typically have cubic nonlinearity, the mechanism for the coupling is found to be caused by the cross-softening effect of the fast mode on the slow mode (Feng 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the term non-resonant to distinguish from commonly studied one-to-one, one-to-two, and oneto-three resonances. This type of nonlinear modal coupling was first studied by Nayfeh & Nayfeh (1992) in structural systems. For structural systems, which typically have cubic nonlinearity, the mechanism for the coupling is found to be caused by the cross-softening effect of the fast mode on the slow mode (Feng 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper we will show the presence of modal coupling when no apparent frequency relationships exist between the interacting modes. This work is motivated by the paper of Nayfeh & Nayfeh (1992) on nonlinear structural vibrations. Nayfeh & Nayfeh show that nonlinear modal coupling occurs in linearly independent modes whose frequencies are widely spaced.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we prefer to model the pendulum as a cantilevered vibration "amplifier". Previous research [28] indicated that we might design a system with the opposite parametric condition in order to produce a large-amplitude vibration on the PVDF stalk with lowamplitude high-frequency excitation.…”
Section: Simplified Dynamic System Modelmentioning
confidence: 99%
“…Internal resonances (IRs) under certain conditions also promote energy transfer between non-linear modes [14,[42][43][44][45]. It was explained, both theoretically and experimentally, how a low-amplitude highfrequency excitation can produce a large-amplitude low-frequency response (called energy cascading [46]).…”
Section: Introductionmentioning
confidence: 99%